Effect of X-ray irradiation on development, flight, and reproduction of Spodoptera litura - Jiang, Shan; Fu, Xiao-Wei; Jiang, Shan-Shan; Yang, Xian-Ming; Zhao, Hui-Yuan; Wu, Kongming (Frontiers in Physiology, 2022)
Spodoptera litura is an omnivorous pest that has spread globally. Because irradiation sterilization technology has a great potential for control of S. litura, the effect of 25–150 Gy doses of X-rays on pupal survival, flight and reproductive variables of adult moths were analyzed in this research. The X-ray irradiation with the dose of 25–150 Gy significantly affected the reproductive ability of females. Irradiating male pupae with 25–150 Gy doses of X-rays had no effect on mating, life span, or flight ability of adult moths, but significantly reduced survival and fecundity of their offspring, and the sterility rate of the F1 generation was 52.65–99.9%. The results of logistic curve fitting showed that the sterility impact was 84% at the most appropriate irradiation dose (71.26 Gy). The sterility control was 91% in an indoor mating competition experiment when the release ratio of irradiated males (75 Gy) to nonirradiated males reached 12.6:1. The effects of X-ray irradiation doses on biological variables of S. litura and the most effective release ratio determined here provide a theoretical foundation for using radiation sterilization technology to control S. litura.